TRADE DISPUTE OF INDONESIAN A4 PAPER PRODUCT AGAINST AUSTRALIA AT THE WTO - Trie Hoetamie Chahyaningroem; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Paper and pulp are important industries in Indonesia and ranks tenth as the largest pulp producer in the world, also ranks sixth in the paper industry. In 2017, Australia declared that Indonesia had dumped A4 paper which is exported to its country. Indonesian government is accused of providing subsidies to paper producers through a policy of prohibiting log export that causes Particular Market Situation (PMS). This research describes the dispute the dispute settlement process between the two countries through dispute settlement body WTO.According to neoliberal institutionalism, institution is a mediator to achieve cooperation between countries. Things which include institutions are organizations, bureaucracy, treaties and agreements. In general the institution is identified as a complex relationship between rules and norms. The WTO is a mediator between Indonesia and Australia. Through the WTO, the two countries settled their disputes and reached cooperation. The WTO acts as a forum for dispute resolution which functions as legal law for its member countries.There are three results from this study. First, the Dispute Settlement Body states that Australia had violated two articles in the WTO Anti-Dumping agreement and the allegations of Particular Market Situation (PMS) hadn’t been proven. Second, Australia is recommended to adjust the calculation of the amount of margin dumping that has been set on Indonesia's A4 copy paper products since 20 April 2017. Third, the two countries agreed to implement the recommendation within eight months. Keywords: dispute, trade, A4 paper, WTO, particular market situation, dumping.